2010
DOI: 10.3109/10715762.2010.490837
|View full text |Cite
|
Sign up to set email alerts
|

Methyleugenol reduces cerebral ischemic injury by suppression of oxidative injury and inflammation

Abstract: The present study tested the cytoprotective effect of methyleugenol in an in vivo ischemia model (i.e. middle cerebral artery occlusion (MCAO) for 1.5 h and subsequent reperfusion for 24 h) and further investigated its mechanism of action in in vitro cerebral ischemic models. When applied shortly after reperfusion, methyleugenol largely reduced cerebral ischemic injury. Methyleugenol decreased the caspase-3 activation and death of cultured cerebral cortical neurons caused by oxygen-glucose deprivation (OGD) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 43 publications
5
26
0
Order By: Relevance
“…Recent research by Choi et al (2010) indicated that ME may have positive effects on human health as well. Based on their studies, ME may reduce cerebral ischemic injury through suppression of oxidative injury and inflammation (Choi et al 2010).…”
Section: Methyl Eugenol and Human Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research by Choi et al (2010) indicated that ME may have positive effects on human health as well. Based on their studies, ME may reduce cerebral ischemic injury through suppression of oxidative injury and inflammation (Choi et al 2010).…”
Section: Methyl Eugenol and Human Healthmentioning
confidence: 99%
“…Based on their studies, ME may reduce cerebral ischemic injury through suppression of oxidative injury and inflammation (Choi et al 2010). The chemical also decreased activation of an enzyme, caspase-3, and the death of cultured cerebral cortical neurons through oxygen— glucose deprivation for one hour.…”
Section: Methyl Eugenol and Human Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…It is used as a flavoring agent in foods such as jellies, baked goods and ice cream and as a fragrance in soaps, lotions and perfumes. This compound is a central nervous system depressant with anesthetic, hypothermic, antianaphylaxis, antinociceptive, anti-inflammatory, myorelaxant and anticonvulsant properties (Abdo et al, 2001;Choi et al, 2010). This is the first report, to our knowledge, about the gastroprotective activity of methyleugenol on ethanol-induced gastric lesions.…”
Section: Discussionmentioning
confidence: 84%
“…Cerebral ischemia reperfusion and local cell debris have a strong cytotoxic effect in the brain parenchyma after middle cerebral artery occlusion (MCAO). The cytotoxic response occurs within minutes of the onset of cerebral ischemia and involves proinflammatory responses, oxidative stress, neurologic damage, and cell death (Choi et al, 2010). Inflammation leads to increased permeability of the BBB, and blood may be discharged from damaged vessels.…”
Section: Introductionmentioning
confidence: 99%